Off-Cycle Emissions of Particle Number from Gasoline and DPF Diesel Passenger Cars in High-Load Conditions - Hiroyuki Yamada; Taichi Kimura; Hidenori Konno; Yoshinori Kondo (Atmosphere, 2023)
To evaluate regulated gases and solid particle number (SPN) emissions in high-load off-cycle conditions, two diesel vehicles with a diesel particulate filter (DPF) and a urea selective catalytic reduction (SCR) system, respectively, and four gasoline port fuel injection (PFI) vehicles were tested with the worldwide light-duty test cycle, including an extra-high (Ex-hi) phase. All the tested vehicles were developed for the Japanese market and did not comply with the Ex-hi phase. All vehicles exhibited higher CO2 emissions in the Ex-hi phase than in low, the mid and high phases. Increased NOx and SPN10-23 emissions were observed with the DPF vehicle. These increased emissions were due to the occurrence of passive regeneration of the DPF, and the urea SCR system was stopped as a result. The small gasoline PFI cars showed increased CO and SPN emissions in the Ex-hi phase. These emissions were due to enrichment control, which occurred in a quite high load operation condition. The feature of higher emissions with enrichment control differed from that observed in a warming-up process in the cold-start mode. SPN23 increased mainly in the warming-up process, whereas SPN10-23 increased in the Ex-hi phase with enrichment control. Hybrid vehicles seem to have fewer opportunities to show the enrichment control due to motor assist.